Past, Present and Future of Planting Teak in the Andamans - Naidu, K. K. (Indian Forester, 1957)
The lack of sustained attempts in the past and unsuited techniques resulted in abandoning the planting of teak some 25 years back. Recent attempts adopting modern methods have shown good promise. The future looks bright.